104 Accuracy of objective handwriting assessment for differentiating Parkinson's disease from tremulous Subjects Without Evidence of Dopaminergic Deficits (SWEDDs): an FP-CIT validated study. Issue 3 (9th February 2012) - Bain, P; Wang, L; Gontu, V K; Bajaj, N P S
Abstract : Handwriting is commonly performed in the clinical analysis of tremor and Parkinson's disease (PD). In this study we analysed the accuracy of objective measurement of handwriting samples for distinguishing 27 PD cases (22 with tremor dominant (TDPD) and five with postural instability gait disorder (PIGD) subtypes) from 39 tremulous SWEDDs cases (31 dystonic tremor (DT), six indeterminate tremor syndrome, one essential tremor, one vascular parkinsonism). All analyses were carried out by an observer blinded to the clinical details and supplied with standardised handwriting specimens, from which the sentence length, mean height of the letter "d" and 3d-Index [(d1−d2) + (d1−d3) + (d2−d3)] (a measure of progressive micrographia, where d1 is the height of the first letter d etc) were measured. A [123I] FP-CIT SPECT scan was performed on every case, except for 5 with PIGD. The results showed that the sentence length was significantly smaller in PD than the SWEDDs or DT cases (p=0.031 and p=0.0056 respectively) and the mean d-height, was also smaller in PD than SWEDDs or DT (p=0.0014 & p=0.0002) but not the 3d-index. The sensitivity and specificity for distinguishing SWEDDs from PD by sentence length (cut at 96 mm) was 67% and 79% and for DT from PD was 67% and 77% respectively. The standard sentence length >130 mm was only seen in DT and <55 mm only in PD. For mean d-height (cut at 5.6 mm) the sensitivity and specificity was 84% and 46% for SWEDDs vs PD and 84% and 55% for DT vs PD. A d-height >6.0 mm was only seen in DT. These results indicate that looking at letter height and sentence length provides useful clinical information for distinguishing DT and SWEDDs cases from PD.